Պատվոժապավենների ծագումը, գործառույթն ու խորհրդաբանությունը Կաթողիկոսի հանդերձանքի համալիրում - Սոֆի Խաչմանյան (ՀՀ ԳԱԱ հրատ.)
В статье обсуждаются некоторые вопросы исторического развития, функции и семиотики почетных лент: ораря и омофора (наплечник), которые являются частью ритуального одеяния служителя Армянской Апостольской Церкви, в частности Католикоса.This article discusses the historical development, usage and symbolism of ritual honorary ribbons. The ribbons are called the stole, epitrachelion and pallium, and are included in the clergy’s and Catholicos ’vestments’ complex of the Armenian Apostolic Church.
Keywords: Arts; Christianity; Armenian church; Fine Arts